Investigation of the Effects of Salinity Exposure on Immune Defense, Morphology, and Gene Expression in the Gills of Macrobrachium nipponense - Shubo Jin; Rong Zhou; Hongtuo Fu; Wenyi Zhang; Hui Qiao; Yiwei Xiong; Sufei Jiang (Antioxidants, 2025)
Macrobrachium nipponense is an important economic freshwater species in China. Previous research has found that M. nipponense can reproduce under salinity conditions of 10 parts per thousand (ppt) and exhibits a strong ability to adapt to salinity changes in the aquatic environment. The aim of the present study was to identify the molecular mechanism of M. nipponense in terms of saline acclimation by identifying changes in immune response, morphology, and gene expression in the gills under a salinity of 10 ppt. The findings revealed that salinity exposure dramatically stimulated the activities of MDA, Ca2+Mg2+-ATPase, and CAT, reaching a peak on Day 7 (p < 0.05), indicating that these antioxidant enzymes play essential roles in protecting the body from the damage caused by saline treatment. In addition, we found no obvious morphological changes in the gills, indicating that M. nipponense can adapt well to water environments with such salinity. Transcriptome profiling analysis identified 168, 434, and 944 differentially expressed genes (DEGs) when comparing S0 vs. S1, S1 vs. S4, and S4 vs. S7, respectively. Furthermore, lysosome, apoptosis, amino sugar, and nucleotide sugar metabolism; the cGMP-PKG signaling pathway; pancreatic secretion; and the calcium signaling pathway represented the main enriched metabolic pathways of DEGs in the present study. Lysosome, apoptosis, amino sugar, and nucleotide sugar metabolism and the cGMP-PKG signaling pathway are immune-related metabolic pathways, while pancreatic secretion is an energy-metabolism-related metabolic pathway, suggesting that the immune response and energy metabolism play essential roles in the regulation of saline acclimation in this species. The results from the quantitative real-time PCR analyses of the DEGs were consistent with those from RNA-Seq, indicating the accuracy of the present study. This study provides valuable evidence for the acclimation of M. nipponense to high-salinity aquatic environments, thus indicating the potential for this species to be used in aquaculture programs in saline and alkaline water regions.